Synthesis and Characterization of Fluorapatite-Copper(II) Oxide with Sol-Gel Method as an Antibacterial Biomaterial - Manasye Erlangga; Charlena Charlena; Irma Herawati Suparto (Jurnal Kimia Sains dan Aplikasi, 2024)
One of the calcium phosphate compounds that can be used as an antibacterial material for coating dental implants is fluorapatite (FAp). This research aims to synthesize FAp at three different sintering temperatures (600, 800, and 1000°C), copper(II) oxide (CuO), and fluorapatite-copper(II) oxide (FAp-CuO) using the sol-gel method, and test the antibacterial properties of the synthesized products. The sol-gel technique proved successful in synthesizing FAp, with optimal results observed at a sintering temperature of 1000°C, achieving a crystallinity level of 90%. Analyses conducted using X-ray diffractometer, Fourier-transform infrared spectrometer, and scanning electron microscope-energy dispersive X-ray spectrometer revealed FAp as the dominating phase, exhibiting Ca/P and P/F ratios of 1.84 and 4.67, respectively. In FAp-CuO, replacing Ca2+ with Cu2+ ions lowered the average crystallite size, crystallinity, and Ca/P ratio. FAp, CuO, and FAp-CuO all displayed antibacterial activities against S. aureus and E. coli, with FAp-CuO having the maximum average inhibitory zone diameters of 0.243 and 1.397 mm, respectively.